2016
DOI: 10.1016/j.intfin.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, structure and growth: New data, method and results

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…Therefore, it is necessary to analyse each aspect and adjust the policies accordingly. The results are summarized in Table 9 , and the influences of FST and FGR [ 98 ] are not statistically significant, so we will not discuss the two indicators.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to analyse each aspect and adjust the policies accordingly. The results are summarized in Table 9 , and the influences of FST and FGR [ 98 ] are not statistically significant, so we will not discuss the two indicators.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The findings show that, GDP growth has dominant indicate on the financial development, while stock market dominance reflect a lower influence. Luintel et al (2016) found that, marketbased financial system account for a sizable economic influence on the high-income countries than the middle and low income nations. Vithessonthi and Kumarasinghe (2016) analyzed the effect of financial development and international trade on stock market integration in 15 Asian developed and developing economies.…”
Section: Introductionmentioning
confidence: 99%
“…They were quick to add that financial structure has no significance in the middle-and low-income countries. Yeh and Lin (2013) and Gambacorta, Yang, and Tsatsaronis (2014), however, reported a non-linear relationship between financial structure and economic growth and that these relationships exist in developing countries, contrary to Luintel et al (2016). Other studies in this class include Tadesse (2005), Lin, Sun, and Jiang (2009) and Rajan and Zingales (2004).…”
Section: Literature On the Relationship Between Financial Structure Amentioning
confidence: 99%